Pelatihan penggunaan quizizz untuk mengurangi kecemasan ujian dan meningkatkan manajemen waktu pada mahasiswa - Ekawati, Dessy; Baderi; Nurul Azmi (LP4M STIKes Karsa Husada Garut, 2024)
Introduction: Time management among students during exams is in a concerning state, with many overwhelmed by scheduling study plans, leading to severe anxiety that disrupts mental health and academic performance. This study aimed to examine the effectiveness of Quizizz training in reducing exam anxiety and enhancing time management skills among students. Methods: This study employed a Service Learning approach to train students in managing exam anxiety and improving time management skills through the use of the Quizizz platform. Intensive training and workshops were conducted for 30 students from ITSKes ICME Jombang. Results: The Wilcoxon statistical test revealed that Quizizz training significantly reduced exam anxiety (p = 0.003) and improved time management skills (p = 0.004). Conclusion: The use of Quizizz is effective in supporting students' mental readiness and skills in managing exams.